Case report: The effective response to pembrolizumab in combination with bevacizumab in the treatment of a recurrent glioblastoma with multiple extracranial metastases - Yang, Gang; Fang, Yu; Zhou, Ming; Li, Wei; Dong, Dapeng; Chen, Jing; Da, Yong; Wang, Kunpeng; Li, Xinru; Zhang, Xiaoyan; Ma, Tonghui; Shen, Ge (Frontiers in Oncology, 2022)
Multiple extracranial metastases of recurrent glioblastoma are rare and often indicate a very poor prognosis. The main conventional treatments are chemotherapy, radiotherapy, chemoradiotherapy or antiangiogenic therapy. Median overall survival is 2.3 to 6 months after the detection of extracranial metastases, and to date, there is no effective treatment for these patients. Herein, we report a recurrent glioblastoma patient with lung metastasis treated with a combination therapy containing bevacizumab and pembrolizumab due to overexpression of PD-L1 and the absence of driver mutations. The progression-free survival was 11 months from lung metastases to bone metastases. This combination treatment was further used as maintenance therapy for another 11 months after bone metastasis and secondary dorsal metastasis because there was no suitable treatment alternative. The overall survival was 27 months after lung metastases, which is much longer than previously reported cases. To our knowledge, this was the first effective use of bevacizumab plus pembrolizumab in a glioblastoma patient with extracranial metastases. Furthermore, this was the first time that bevacizumab plus pembrolizumab was used as a maintenance treatment in glioblastoma, with 11 months of response. Importantly, we showed that such combination therapy may be a novel and effective therapy for glioblastoma patients with extracranial metastases.